Platelet Count Might Be Associated With the Closure of Hemodynamically Significant Patent Ductus Arteriosus - Zhong, Junyan; Lin, Binchun; Fu, Yongping; Yu, Yanliang; Zhao, Jie; Zhao, Depeng; Yang, Chuanzhong; Chen, Xueyu (Frontiers in Pediatrics, 2021)
Background: Platelet-rich thrombosis leads to the occlusion of arteries. Whether the association between platelet count and closure of hemodynamically significant patent ductus arteriosus (hsPDA) exists remains inconclusive. Given that neonatal platelet count is significantly affected by infection, this study aims to evaluate the association of platelet parameters before ibuprofen treatment with the closure of hsPDA in very low birth weight (VLBW) infants without concurrent infection. Methods: A retrospective study was conducted at the NICU of Shenzhen Maternity and Child Healthcare Hospital from January 2016 to August 2020. VLBW infants diagnosed with hsPDA, treated with oral ibuprofen and without concurrent infection were included in this study. The platelet parameters were retrieved from the whole-blood test routinely performed within 24 hours before starting treatment of oral ibuprofen. A multiple regression model was built to evaluate the association between platelet parameters before ibuprofen treatment and successful closure of hsPDA. Results: A total of 129 premature infants with hsPDA were analyzed in this study. After oral ibuprofen treatment, successful closure of hsPDA was achieved in 70 (54.3%) infants. The gestational age at birth and birth weight in infants with successful or failed closure of hsPDA after ibuprofen treatment were respective 28.3 vs 27.6 weeks (p=0.016) and 1120 vs 960 grams (p=0.043). The rate of mechanical ventilation in infants with successful closure of hsPDA was significantly lower compared to those with failed closure of hsPDA, 31.4% vs 54.2%, p=0.014. The platelet count in infants with successful closure of hsPDA after ibuprofen treatment was significantly higher compared to those with failed closure of hsPDA, 212 vs 183 (in a unit of 10^9/l), respectively (p=0.024). Multivariate logistic regression analysis showed that a higher platelet count (≥181*10^9/l) before ibuprofen treatment was independently associated with successful closure of hsPDA [odds ratio 2.556, 95% confidence interval (1.101-5.932), p=0.029]. Conclusion: The findings in this study suggest that a higher platelet count before oral ibuprofen treatment may predict the probability of successful closure of hsPDA in VLBW infants.